The single market and EMS instability - Paul J. J. Welfens (Intereconomics, 1994)
The following analysis of the 1992/93 crisis of the European Monetary System finds that the unfolding of the single market dynamics will make European Monetary Union a difficult stage to achieve. Further monetary integration is only feasible if full employment and sustained growth are achieved in the EC. The Maastricht Treaty needs some add-ons if economic and monetary union is to succeed.
Keywords: 330; European Monetary System